2021
DOI: 10.1002/pol.20210592
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of organometallic complexes in emerging photovoltaics

Abstract: Organometallic complexes (OMCs) consisting of organic and metal active moieties have shown immense potential for application in solar cells. The diverse structure, rich porosity, and unique charge centers of OMCs enable them to be functional in solar cells. In this review, we introduced four types of OMCs, such as crown organometallic complexes, β-diketone metal complexes, cyclometallic complexes, and main chain metal-containing polymers, providing an in-depth analysis of the structure-performance relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 368 publications
(354 reference statements)
0
21
0
Order By: Relevance
“…In addition to small molecules and polymers, organometallic compounds could be successfully developed as dopant-free HTMs for PSCs. 154,155 Among them, metal phthalocyanines (MPc) have attracted great interest as HTMs for PSCs, owing to their low synthesis cost and excellent stability. 156,157 In 2020, Cheng's group reported a methoxy substituted copper(II) phthalocyanine CuPc-(OMe) 8 that exhibited comparable hole mobility (1.1 Â 10 À3 cm 2 V À1 s À1 ) and conductivity properties (1.4 Â 10 À4 S cm À1 ) compared with the doped Spiro-OMeTAD.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…In addition to small molecules and polymers, organometallic compounds could be successfully developed as dopant-free HTMs for PSCs. 154,155 Among them, metal phthalocyanines (MPc) have attracted great interest as HTMs for PSCs, owing to their low synthesis cost and excellent stability. 156,157 In 2020, Cheng's group reported a methoxy substituted copper(II) phthalocyanine CuPc-(OMe) 8 that exhibited comparable hole mobility (1.1 Â 10 À3 cm 2 V À1 s À1 ) and conductivity properties (1.4 Â 10 À4 S cm À1 ) compared with the doped Spiro-OMeTAD.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%
“…It has been demonstrated that by selecting a suitable combination of metal ions and organic ligands, these coordination complexes can lead to aligned energy levels and display moderate electron mobility, thus facilitating efficient charge extraction and transport. 114,115 Notably, both inverted and regular OSCs have been obtained by using these coordination complex based CILs. Fan and Zhu reported that zirconium acetylacetonate (ZrAcac) is soluble in a range of organic solvents from chloroform to methanol.…”
Section: Coordination Complex Based Hybrid Cilsmentioning
confidence: 99%
“…26 In current state-of-the-art organic photovoltaics, triplet states and charge transfer triplet states have only rarely been considered to improve device efficiencies. 14,27 One of the big challenges is to explore triplet photovoltaic materials that synergistically bear with sufficiently long triplet lifetime, appropriately high triplet energy levels, broad and strong light absorption as well as favorable charge carrier mobilities. 24,25,[28][29][30][31] It is noted that cyclometalated Ir or Pt complexes embedded random terpolymer donors or acceptors demonstrated high PCE up to 17.2%, [32][33][34] which is superior than their metal-free organic copolymers.…”
Section: Introductionmentioning
confidence: 99%